Peningkatan Keterampilan Literasi Membaca Melalui Model Problem Based Learning Pada Pembelajaran Bahasa IndonesiaKelas IV SD Negeri Sendangmulyo 02 - Azizah, Azizah; Wakhyudin, Husni (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2025)
This research was motivated by the problems experienced by fourth grade students at SD Negeri Sendangmulyo 02 in the Indonesian language subject. The purpose of this research is to determine the improvement in reading literacy skills of fourth grade students at SD Negeri Sendangmulyo 02 in Indonesian language subjects using the Problem Based Learning (PBL) learning model. Data collection techniques were carried out using observation, documentation and tests. The indicator of success is known if students get a reading literacy skills score of at least 75 with a completion percentage of 75% from 27 students. The research began with pre-cycle learning with 12 of the 27 grade IV students at SD Negeri Sendangmulyo 02 getting a reading literacy skill score below 75. The average reading literacy skill score they got was only 70.38 with a completion percentage of 56% for the 27 students. Then cycle 1 learning was carried out to deal with these problems using the Problem Based Learning (PBL) learning model with the result that 9 out of 27 students obtained reading literacy skill scores below 75. The average reading literacy skill score they obtained was 75.46 with a percentage 67% completion of 27 students. The research continued in cycle 2 with the final result being an increase from 9 students who did not complete to 6 students. The average score of students' reading literacy skills also increased to 80.55 and the percentage of students' reading literacy skills completion increased to 78%.